1999
DOI: 10.1002/(sici)1521-3773(19990903)38:17<2565::aid-anie2565>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Terthienyl-Based Redox-Switchable Hemilabile Ligands: Transition Metal Polymeric Complexes with Electrochemically Tunable or Switchable Coordination Environments?

Abstract: By controlling the extent of oxidation of the polymeric forms of the new class of isolable, polymerizable terthienyl Ru(II) complexes 1, one can modulate both the binding strength of the polymer backbone for Ru(II) and the electronic nature of the bound metal centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 5 publications
2
28
0
1
Order By: Relevance
“…Ruthenium complexes of phosphin-containing terthiophene ligands 2.320 were synthesized with the aim to prepare oligomers or polymers with redox-switchable hemilabile ligands (Chart 2.52). 392 Interestingly, the ligand that is η 1 -bound to the terminal thiophene was easily displaced when 4 equiv of acetonitrile were added. Spectroelectrochemical investigations of the corresponding electrochemically generated polymer revealed that the ruthenium centers showed a reversible and switchable intramolecular interaction with the polymer backbone.…”
Section: Other Ligand-functionalized Oligothiophenesmentioning
confidence: 99%
“…Ruthenium complexes of phosphin-containing terthiophene ligands 2.320 were synthesized with the aim to prepare oligomers or polymers with redox-switchable hemilabile ligands (Chart 2.52). 392 Interestingly, the ligand that is η 1 -bound to the terminal thiophene was easily displaced when 4 equiv of acetonitrile were added. Spectroelectrochemical investigations of the corresponding electrochemically generated polymer revealed that the ruthenium centers showed a reversible and switchable intramolecular interaction with the polymer backbone.…”
Section: Other Ligand-functionalized Oligothiophenesmentioning
confidence: 99%
“…Mirkin and coworkers have elegantly demonstrated this concept through the electropolymerization of 24. [43] Oxidation of the polymer film results in a 18 cm ±1 shift in the CO infrared stretching frequency. A gradual increase in the level of backbone oxidation could give rise to a gradual shift in the stretching frequency; however, only two discrete stretching bands are observed during this experiment suggesting that holes are localized along the polymer backbone (Fig.…”
Section: Polymers Containing Metals Bound To the Polythiophene Backbonementioning
confidence: 99%
“…Inset: FTIR spectrum of poly-24 (m CO = 1993 cm ±1 ). Reprinted with permission from [43]. Copyright 1999 Wiley-VCH.…”
Section: Type III Polymers With Metals In the Backbonementioning
confidence: 99%
“…The "intramolecular" complexation of ruthenium complexes with a thiophenebased backbone could be modulated electrochemically [545]. On similar thiophenebased polymer electrodes, the ion flux and ion exchange into the polymer could be resolved by scanning ion conductance microscopy [546].…”
Section: Covalently Bound Redox Moietiesmentioning
confidence: 99%